Religious services attendance and college adjustment of Diploma in Computer Science UTM students - Suppiah, Krishnavenee (Universiti Teknologi Malaysia, 2003)

(untitled)
This study intends to investigate the relationship between the frequency of religious services attendance (RSA) and college adjustment of Diploma in Computer Science (DDC) UTM, KL students in terms of gender and achievement. The subjects of this study consist of sixty-nine DDC UTM students. The Student Adaptation to College Questionnaire (SACQ) by Baker and Siryk (1999) and a personal demographic data sheet were used in this study to gather data. The results indicate that: (1) the relationship between college adjustment and frequency of RSA are non-significant and that neither RSA nor gender and GPA scores predict college adjustment of DDC students; (2) there is a significant difference between academic adjustment and frequency of RSA; (3) male DDC students seem to attend religious services more frequently than the female students; and (4) a higher number of high and average achievers seem to frequently attend religious services